Pelatihan Senam Hamil untuk Meningkatkan Kesiapan Persalinan Ibu Hamil - Treasa, Adisty Dwi; Rahmat, Rezqiqah Aulia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Pregnancy is a physiological process that requires optimal physical and psychological preparation for childbirth. One way to achieve this is through prenatal exercise, which has been proven to increase muscle strength, improve breathing, and reduce maternal anxiety. This community service activity aims to improve childbirth readiness through prenatal exercise training for pregnant women in their second and third trimesters. The activity method included education on the benefits of prenatal exercise, demonstrations of exercise movements, and hands-on practice with assistance from health workers. Evaluation was conducted using pre- and post-tests on knowledge and observation of exercise movement skills. The results of the activity showed an increase in participants' knowledge about the benefits of prenatal exercise and their ability to perform the movements correctly. Participants also reported increased self-confidence and preparedness for childbirth. In conclusion, prenatal exercise training is effective in improving both physical and psychological readiness for childbirth. It is hoped that this activity can continue with the support of health facilities and Posyandu (Integrated Service Post) cadres so that its benefits can be felt more widely.